Von der Messaufgabe zum Sensorsystem - Henning, Bernd
Ultraschallsensoren werden heute in der Industrie vielfach erfolgreich für die verschiedensten Messaufgaben eingesetzt und ständig weiterentwickelt. Wesentliche aktuelle Entwicklungen zielen auf die Erweiterung der Funktionalität (adaptierbare Abstrahlcharakteristik, scannende Sensoren …), die Erhöhung der Zuverlässigkeit, die Miniaturisierung sowie auf die Reduktion der Gerätekosten (Materialsubstitution) und Fertigungskosten (Konstruktion und Montage).

Ultrasonic Nondestructive Testing of composite materials using disturbed coincidence conditions - Bause, Fabian; Olfert, Sergei; Schröder, Andreas; Rautenberg, Jens; Henning, Bernd; Moritzer, Elmar (Journal of Electronic Measurement and Instrument)

Analyzing the effect of adhered metal electrodes on piezoelectric elements using different types of adhesives - Bause, Fabian; Rautenberg, Jens; Henning, Bernd
Modeling and simulation play a key-role in computer-assisted design of ultrasonic sensors. The accuracy of those numerical or analytical models highly depends on the material dataset chosen as well as on the digitized simplified geometry. Thus, researchers worked on techniques how to measure material datasets of piezoceramics or passive materials (i.e. polymers) for use in simulation [Rau08] [Rup09]. Most computer models neglect the influence of adhesive bonds between those active and passive material components used to form a complete ultrasonic transducer and thus imply perfect interface layers. To gain a more accurate model one need to go further and consider non-perfect interface layers between assembly parts. Because adhesive bonds are neither necessarily isotropic nor homogeneous and their geometric dimensions are very small, we need to define effective material datasets dependent on the model used in simulation. In this contribution the indicator under study is the electric impedance of the active element. We will show the influence of different adhesives used to adhere metal electrodes on piezoceramic discs. Therefore, we use several different types of adhesives (epoxies, cyanoacrylates and perfluorpolyether grease) and different sizes of piezoceramic discs (PIC 255, manufacturer: PI Ceramic GmbH) of the same batch (thickness, diameter). The electrodes have been cut from one plate made of stainless steel using a laser to avoid uncertainty effects due to variations in material-parameters. The probes have been prepared in an air-conditioned Lab with constant temperature and humidity. The indicators considered to identify the effect of those different adhesive films are extracted from the electric impedance of the electromechanical converter.

Ultrasonic distance sensors - An overview and trends - Henning, Bernd; Schröder, Andreas (Journal of Electronic Measurement and Instrument)
Nowadays ultrasonic distance sensors are widely used in automobiles, robotics and in industrial automation. Some functional principles of usable transducers for airborne ultrasonic distance measurements are shown. As every sensor principle, ultrasonic distance sensors have pros and cons which lead to some problems and challenges described below. For the main challenges (crosstalk and blind zone) some trends and solutions are presented.

Vergleich zwischen der Schlierenmethode nach Toepler und der Hintergrundschlierenmethode zur Bestimmung akustischer Grössen eines Ultraschallwandlers - Olfert, Sergei; Henning, Bernd
Es gibt unterschiedliche Methoden, um räumliche Schallwechseldruckverteilungen in Flüssigkeiten zu erfassen. Viele dieser Verfahren haben zwei Nachteile. Sie sind zum einen invasiv, beeinflussen somit die sich ausbreitende Ultraschallwelle, und zum anderen sehr zeitaufwendig. Die Visualisierung von Ultraschallfeldern mittels Schlierenmethode ist eine schnelle und einfache Methode, um zweidimensionale Schallfelder nichtinvasiv zu analysieren. Ein besonderer Vorteil besteht darin, dass man unmittelbar resultierende Veränderungen im Schallfeld zum Beispiel bei Frequenzänderung, Sensorausrichtung… beobachten kann. In diesem Beitrag werden zwei dieser Verfahren vorgestellt. Die modifizierte Schlierenmethode nach Toepler, das im Weiteren als modifizierte Schlierenmethode bezeichnet wird, und die Hintergrund-schlierenmethode, das sich bisher hauptsächlich zur Strömungsvisualisierung etabliert hat [1]. Im ersten Teil werden beide Messverfahren erläutert, die realisierten Messaufbauten sowie Einsatzmöglichkeiten für die Schallfeldcharakterisierung kurz vorgestellt. Im zweiten Teil werden beide Verfahren verglichen und die Vor- und Nachteile bezüglich ausgewählter Messaufgaben bewertet.

Utilizing an Analytical Approximation for c44E to Enhance the Inverse Method for Material Parameter Identification of Piezoceramics - Rautenberg, Jens; Rupitsch, Stefan J.; Henning, Bernd; Lerch, Reinhard (7th International Workshop on Direct and Inverse Problems in Piezoelectricity)
There has been a lot of progress in finding measurable quantities of high in- formation content for the inverse determination of piezoelectric material properties. Since some material parameters (mainly \textgreek{e}S 11, e15and cE 44) do not or only marginally influence the electrical impedance over frequency, it is not sufficient to look only at the electri- cal impedance of discoidal piezoceramics [1]. Moreover, the parameter sensitivities vary with respect to the diameter--thickness ratio of the disc and the design of an ultrasonic transducer's piezoceramic has to match other requirements than those of a good material characterization [2, 3]. That is why it is still desirable to find model based approaches for parameter identification that either keep the technical effort low (e.g., only an impedance measurement) or increase speed of the inversion procedure. In this contribution we answer the question if an additional analytical approximation of cE 44, strictly following the ideas of Theocaris [4], in conjunction with a single measured elec- trical impedance will be sufficient for an accurate simulation of both, electrical impedance and surface normal velocity of a piezoceramic disc. Thereby, the remaining parameters are identified by means of the Inverse Method. Furthermore, we use the parameter ap- proximation as an initial guess and limiting boundary to speed up the inverse algorithm if both, electrical impedance and surface normal velocity are taken into account within the optimization procedure.

Luftultraschall-Abstandsmessung mit verkürztem Mindestabstand - Schröder, Andreas; Henning, Bernd
Bei der Luftultraschall-Abstandsmessung mit einem einzelnen Schallwandler ist der Mindestabstand durch die Sendesignaldauer und die Ausschwingzeit des Schallwandlers begrenzt. Daher führt die Verwendung von codierten Sendesignalen, wie sie z.B. für die Unterscheidung mehrerer Sender genutzt werden können, im Allgemeinen zu einer Vergrößerung des Mindestabstandes. Dieser Beitrag zeigt, dass der Mindestabstand bei codierten Sendesignalen durch eine geeignete Signalverarbeitung, bei der eine Trennung des Sende- und Empfangssignals erfolgt, deutlich verringert werden kann.

Model based separation of transmitted and received signal for single transducer distance measurement applications - Schröder, Andreas; Henning, Bernd
Simultaneous transmitting and receiving (STaR) enhances the utilization of single transducer ultrasound measurement systems. In distance measurement applications the dead zone can be reduced to nearly zero, independent of the transmitted signal. So it is possible to transmit codedsignals to identify different sensors without increasing the minimum distance. The electrical transducer signal consists of the electrical transmitted and received signal. A separation of these two signals can be done with a mathematical model of the electrical system. For this purpose it is necessary to digitize the electrical transducer signal. Due to the relative small amplitude of the received signal compared to the transmitted signal amplitude, a high resolution analog to digital converter (ADC) is needed. This leads to high requirements for the ADC. The necessary resolution limits the sample rate of the ADC. By down mixing the transducer signal using a coherent quadrature demodulation (CQD), as used in many high frequency ultrasound applications, the sample rate of the ADC can be reduced. In this contribution an airborne ultrasound distance measurement system with reduced dead zone is used to analyze the effects of this concept to the signal conditioning, system identification and system performance. The approach is compared with a system without CQD and an ADC with a lower resolution but a higher sample rate. By analyzing the pros and cons of both systems the usability of a CQD based system for a STaR application is evaluated. The distance measurement system used for the experiments is based on a 40 kHz airborne ultrasonic transducer. A gyrator based transmit amplifier delivers a system bandwidth of about 10 kHz. In the experiments, coded transmitted signals are used to measure the distance to a metal reflector. The main objectives are short distances between 0 mm and 200 mm. Here a separation of transmitted and received signal is necessary. The reflector distance is calculated by a cross correlation between transmitted and received signal.

Finite element simulation of single ultrasonic transducer with segmented electrodes to adjust the directional characteristic - Unverzagt, Carsten; Henning, Bernd
For many applications like level measurement and industry robotics it is of advantage if the directional characteristic of an ultrasonic transducer is changeable or adaptable for the improvement of spatial resolution. Often this goal is reached with the use of ultrasonic transducer arrays, which elements are driven with phase shifted excitation signals. One disadvantage of these solutions is the great effort for building such an array and the multi-channel sensor electronics. In this contribution the directional characteristic of a single air transducer with segmented electrodes is analyzed. Therefore a variable script based finite element model is used to discover the influence of different electrode configurations on the directional characteristic of a single piezoceramic transducer. Especially the influence on the angle of beam and the near field length are evaluated. The used variable model permits an optimization of the configuration with regards to the mentioned criteria. The findings will be used for the development of a level measurement system for bulk solids.
Keywords: Elektrode

Utilizing an Analytical Approximation for c44E to Enhance the Inverse Method for Material Parameter Identification of Piezoceramics - Rautenberg, Jens; Rupitsch, Stefan J.; Henning, Bernd; Lerch, Reinhard (7th International Workshop on Direct and Inverse Problems in Piezoelectricity)
There has been a lot of progress in finding measurable quantities of high in- formation content for the inverse determination of piezoelectric material properties. Since some material parameters (mainly \textgreek{e}S 11, e15and cE 44) do not or only marginally influence the electrical impedance over frequency, it is not sufficient to look only at the electri- cal impedance of discoidal piezoceramics [1]. Moreover, the parameter sensitivities vary with respect to the diameter-thickness ratio of the disc and the design of an ultrasonic transducer's piezoceramic has to match other requirements than those of a good material characterization [2, 3]. That is why it is still desirable to find model based approaches for parameter identification that either keep the technical effort low (e.g., only an impedance measurement) or increase speed of the inversion procedure. In this contribution we answer the question if an additional analytical approximation of cE 44, strictly following the ideas of Theocaris [4], in conjunction with a single measured elec- trical impedance will be sufficient for an accurate simulation of both, electrical impedance and surface normal velocity of a piezoceramic disc. Thereby, the remaining parameters are identified by means of the Inverse Method. Furthermore, we use the parameter ap- proximation as an initial guess and limiting boundary to speed up the inverse algorithm if both, electrical impedance and surface normal velocity are taken into account within the optimization procedure.

An improved mode-tracing algorithm to compute dispersion curves of acoustic waveguides - Bause, Fabian; Rautenberg, Jens; Henning, Bernd
Semi-analytical approaches for the description of dispersion in acoustic waveguides are based on root finding in a characteristic function. A mode-tracing algorithm helps to find all solutions of this problem by consecutively bracketing single roots. In this contribution we present a multistage and adaptive mode-tracing algorithm, which uses an adaptive step size for the prediction of consecutive solutions as well as an adaptive estimation of the search space around these predictions. Furthermore we present a validation stage to ensure the correlation between consecutive solutions alias waveguide modes.

Entwicklung und Parametrisierung eines Mode-Tracing Algorithmus für halbanalytische Solver - Bause, Fabian; Rautenberg, Jens; Henning, Bernd
Die computergestützte Simulation geführter elastischer Wellen in ein- oder mehrschichtigen Wellenleitern ist in vielen Bereichen der akustischen Forschung ein essentielles Modellierungswerkzeug. Sie ermöglicht, auch in komplexen Systemen, eine Beschreibung der Wellenausbreitungsvorgänge, deren analytische Lösung zu aufwendig oder nicht durchführbar ist. Im ersten Abschnitt dieses Beitrags wird auf den halbanalytischen Solver bzw. die mathematische Formulierung des die Wellenausbreitung beschreibenden Problems eingegangen. Der zweite Abschnitt beinhaltet den mehrstufigen Aufbau eines Tracing-Algorithmus, welcher den Lösungsraum des Solvers adaptiv einschränkt, so dass Leistungsfähigkeit und Robustheit des Gesamtalgorithmus gestärkt werden.

Improved system identification for simultaneous transmitting and receiving in single transducer applications - Schröder, Andreas; Henning, Bernd
In single transducer applications it would be desirable if the received electrical signal (echo signal) could be evaluated during transmitting. Thereby it is possible to measure very short distances. There are some solutions to realize this, but they have one limitation which prevents the usage in many industrial application. They need a calibration without an echo. The main problem is that this calibration has to be repeated whenever the process parameters like temperature or acoustic load change. This contribution presents an approach which uses a model identification based on different successive measurements which may include echoes. It is done by an impulse response decomposition followed by a principle component analysis. Results of measurements with sine burst excitation and a reflector in front of the transducer are presented.

Interfaceschaltung für einen simultanen Sende- und Empfangsbetrieb mit einem einzelnen Ultraschallwandler - Schröder, Andreas; Henning, Bernd
In der Ultraschallmesstechnik (Abstandsmessung, NDT) ist es zur Detektion naheliegender Reflektoren bzw. zur Erfassung der Medienrückwirkung (Wirkung der akustischen Last) notwendig, die Empfangssignale auszuwerten, noch während der Schallwandler mit dem Sendesignal angesteuert wird oder die Sendesignalenergie am Schallwandler noch nicht ausreichend abgeklungen ist. In diesem Beitrag wird eine Schaltung zur Kompensation des Sendesignals beschrieben, welche die unmittelbare Auswertung des Empfangssignals ermöglicht.

Messrohr für einen Ultraschall-Durchflussmesser und Ultraschall Durchflussmesser - Schröder, Andreas; Rautenberg, Jens; Behlen, H.; Ziegler, Horst; Unverzagt, Carsten; Gaugler, Ulrich; Glatter, T.; Horrn, R.; Kroemer, H.; Schmidt-Schoenian, Axel; Sonnenberg, Hans-Michael; Henning, Bernd

Evaluation of cost functions for FEA based transducer optimization - Schröder, Andreas; Rautenberg, Jens; Henning, Bernd (Physics Procedia)

A new method of spatial filtering for Schlieren visualization of ultrasound wave fields - Unverzagt, Carsten; Olfert, Sergei; Henning, Bernd (Physics Procedia)

PC gestützte Entwicklung von Ultraschallsensoren - Henning, Bernd

Adaptives Mode-Tracing und numerische Stabilisierung modellierter Anregungsstrukturen für die halbanalytische Simulation geführter Wellen - Bause, Fabian; Henning, Bernd

Halbanalytische Modellierung akustischer Wellenausbreitung im ein- und mehrschichtigen Wellenleiter - Bause, Fabian